Nuclear Disarmament and Non-Proliferation - Lodgaard, Sverre (Taylor & Francis, 2025)
A PDF version of this book is available for free in open access via www.tandfebooks.com as well as the OAPEN Library platform, www.oapen.org. It has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license and is part of the OAPEN-UK research project. This book examines the current debate on nuclear non-proliferation and disarmament, notably the international non-proliferation regime and how to implement its disarmament provisions. Discussing the requirements of a new international consensus on nuclear disarmament and non-proliferation, this book builds on the three pillars of the nuclear non-proliferation treaty (NPT): non-proliferation, disarmament and peaceful uses of nuclear energy. It reviews the impact of Cold War and post-Cold War policies on current disarmament initiatives and analyses contemporary proliferation problems: how to deal with the states that never joined the NPT (India, Pakistan and Israel); how states that have been moving toward nuclear weapons have been brought back to non-nuclear-weapon status; and, in particular, how to deal with Iran and North Korea. The analysis centres on the relationship between disarmament and non-proliferation in an increasingly multi-centric world involving China and India as well as the US, the European powers and Russia. It concludes with a description and discussion of three different worlds without nuclear weapons and their implications for nuclear disarmament policies. This book will be of great interest to all students of arms control, strategic studies, war and conflict studies, and IR/security studies in general Sverre Lodgaard is a Senior Research Fellow at the Norwegian Institute of International Affairs, Oslo